Immigrant Digital Generation Teacher Efforts in Investing Digital Literacy in Early Childhood Education - Fitriyah, Qonitah Faizatul; Qaidatiningsih, Salmarani Putri; Nafisah, Shafa Oktavia (Early Childhood Research Journal (ECRJ), 2023)
Learning difficulties that many students experience are learning concentration, management of learning materials, storage of learning outcomes, and exploration of stored learning outcomes. With digital literacy, it can increase student independence in finding solutions to problems that arise during learning using various digital sources. However, this is a problem for teachers of the digital immigrant generation because of the large difference in the generation gap. The output targets are (1) research reports on teachers' efforts to instill digital literacy for early childhood, (2) research articles published in the journal "Cakrawala Dini" accredited national journal Sinta 3. This research is a qualitative research with a case study type. The object of this research is the digital immigrant generation teacher at Aisyiyah Kartasura Kindergarten. Data collection techniques used are through observation, interviews, and documentation. While testing the validity of the data includes: internal validity, external validity, reliability, and objectivity. Data obtained by in-depth interviews can be analyzed by open-coding.